Global Trend in Medication Safety Tools and Technologies: Scoping Review - Sri Ayu Candra A Misali; Humairatun Zakiyah; Afrianti Pakalessy; Sabrina Rahmatillah Azhar; Alrega Widya Nerienecta; Arum Aripurnami; Ariani Arista Putri Pertiwi; Ayu Anita (LPPM Universitas Harapan Bangsa, 2024)
Background: Patient safety is a practice that focuses on preventing, reducing, and avoiding injuries that can occur to patients during medical care. One of the efforts is the safety and monitoring of drugs to ensure safety standards for patients. Medication errors are a significant patient safety problem and a critical indicator in assessing patient safety. The development of technology and informatics in nursing can help prevent medication errors. Objectives: To identify the tools used to address medication safety. Methods: Literature review using the PRISMA model approach. The analysis included articles from seven electronic databases published in the last five years. Results: 54 articles were collected and 15 relevant articles were selected. These studies are compiled from various countries and describe the tools used in implementing medication safety. Conclusion: The tools and technologies found can help medicinal programs and prevent errors in the care and administration of drugs in various hospitals worldwide.